ANALISA PERHITUNGAN PAJAK PENGHASILAN PASAL 21, SEBAGAI PERENCANAAN PAJAK PENGHASILAN BADAN KANTOR JASA AKUNTAN SURABAYA - Jessica Fernanda; Lusy Lusy (STIE PGRI Dewantara Jombang, 2022)
As the biggest source of state revenue, tax that is directly related to employees is income tax article 21. This study aims to analyze the calculation of income tax article 21 with 2 methods (net, gross, and gross up) as an effort to plan corporate income tax on one Accountant Service Office in East Surabaya. The research object is located in the city of Surabaya and is engaged in services such as bookkeeping services, tax services, financial consulting services, and so on. This study uses a qualitative approach method supported by quantitative data. The data used are salary data for permanent employees in 2017, the company’s article 21 PPh calculation, and PPh regulation. The conclusion from this study is that the Gross Up method is the best and most effective method for Corporate Tax Planning. The Gross Up method allows companies to provide tax benefits to employees and can be used as a deduction from the company’s gross income so that the Corporate Income Tax paid is smaller. This research is limited to one company only, the development of which can be done by distributing questionnaires related to the calculation of income tax article 21.